1999
DOI: 10.1111/j.1939-1676.1999.tb02215.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Some Plasma Clearance Methods for Estimation of Glomerular Filtration Rate in Dogs with Pyometra

Abstract: The purpose of the present study was to compare different pharmacokinetic models for estimation of glomerular filtration rate (GFR) in 50 dogs with pyometra. GFR was estimated by plasma clearance (CLplasma) of iohexol by four 1-compartment methods (CL1c), a 2-compartment method (CL2c), and the trapezoidal method (CLtr). Regression analysis was performed to establish correction formulas for prediction of CLtr from the CL1c values and to find optimal times of sampling. Standardization of clearance values to body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…One of these procedures relates GFR to the extra- cellular fluid volume (ECFV). Heiene et al [23] showed that PCio standardized by the extracellular fluid volume (ECFV) in dogs results in the smallest coefficient of variation in a comparison with other standardization procedures (PCio/BW and PCio/BSA), but the PCio/ECFV value maintains its relationship with BW. In the present study, PCio could not be standardized by ECFV because plasma clearance using the 2-compartment model is needed to calculate ECFV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these procedures relates GFR to the extra- cellular fluid volume (ECFV). Heiene et al [23] showed that PCio standardized by the extracellular fluid volume (ECFV) in dogs results in the smallest coefficient of variation in a comparison with other standardization procedures (PCio/BW and PCio/BSA), but the PCio/ECFV value maintains its relationship with BW. In the present study, PCio could not be standardized by ECFV because plasma clearance using the 2-compartment model is needed to calculate ECFV.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in healthy dogs, as the standardization of PCio by BSA in cats can counteract the effect of BW, PCio/BSA may be more adapted for assessment of GFR than PCio/BW in cats. In humans and animals, standardization procedures for GFR have been proposed because GFR depends on body size [23,24,30]. One of these procedures relates GFR to the extra- cellular fluid volume (ECFV).…”
Section: Discussionmentioning
confidence: 99%
“…The results presented herein are in agreement with previous studies in dogs and cats, with the same or a different tracer and support of the use of a simplified plasma clearance method for routine glomerular filtration rate (GFR) estimation in clinical practice. 9,20,21 Normalization was performed before calculating error associated with simplified methods, because normalized clearances are used in clinical practice. Unnormalized clearances have a larger range than normalized clearances with a potential positive effect on regression analysis and calculation of coefficient of determination.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility to minimize error when using 2 samples is to 1st calculate clearance by use of the AUC corresponding to the late monoexponential part of the time-concentration curve, and to correct the calculated clearance with an empirically established equation, to take into account, the early phase. 5,8,9,20 Both methods have been validated, but the method used in this study has been shown to yield less error in clearance estimation. 9 The difference in the best combination of sampling times for dogs (5 and 120 minutes) and cats (20 and 180 minutes) found in this study probably reflects differences in the population and mean clearance.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 10 mg/kg on days 1, 2, and 7 in combination with antibiotics was successful in treating 21 bitches and 4 cats with only 1 recurrence over a 14-month period of observation. 60,[66][67][68] No side effects were observed, and 2 of the bitches went on to be successfully bred. 68 Although the availability and high cost of these agents limit current use of these agents in the United States, with time they may become a valuable tool in the treatment of pyometra.…”
Section: Pyometramentioning
confidence: 99%